Effects of NPY and the specific Y1 receptor agonist [D-His(26)]-NPY on the deficit in brain reward function and somatic signs associated with nicotine withdrawal in rats - Rylkova, Daria (2008)
Tobacco addiction is a chronic disorder that is characterized by dysphoria upon smoking cessation and relapse after periods of abstinence. Previous research suggests that Neuropeptide Y (NPY) and Y1 receptor agonists attenuate negative affective states and somatic withdrawal signs. The aim of the present experiments was to investigate the effects of NPY and the specific Y1 receptor agonist [D-His(26)]-NPY on the deficit in brain reward function and somatic signs associated with nicotine withdrawal in rats. The intracranial self-stimulation procedure was used to assess the effects of nicotine withdrawal on brain reward function as this procedure can provide a quantitative measure of emotional states in rodents. Elevations in brain reward thresholds are indicative of a deficit in brain reward function. In the first experiment, NPY did not prevent the elevations in brain reward thresholds associated with precipitated nicotine withdrawal and elevated the brain reward thresholds of the saline-treated control rats. Similar to NPY, [D-His(26)]-NPY did not prevent the elevations in brain reward thresholds associated with precipitated nicotine withdrawal and elevated the brain reward thresholds of the saline-treated control rats. Neither NPY nor [D-His(26)]-NPY affected the response latencies. In a separate experiment, it was demonstrated that the specific Y1 receptor antagonist BIBP-3226 prevented the NPY-induced elevations in brain reward thresholds. NPY attenuated the overall somatic signs associated with precipitated nicotine withdrawal. [D-His(26)]-NPY did not affect the overall somatic signs associated with precipitated nicotine withdrawal, but decreased the number of abdominal constrictions. Both NPY and [D-His(26)]-NPY attenuated the overall somatic signs associated with spontaneous nicotine withdrawal. These findings indicate that NPY and [D-His(26)]-NPY attenuate somatic nicotine withdrawal signs, but do not prevent the deficit in brain reward function associated with precipitated nicotine withdrawal. In addition, NPY decreases the sensitivity to rewarding electrical stimuli via an Y1 dependent mechanism.